Pemberdayaan Perempuan Melalui Karya Kewirausahaan Untuk Mendorong Ketahanan Ekonomi Keluarga Pada Dharma Wanita Persatuan Balai Taman Nasional Sebangau - Septa Soraida; Ani Mahrita; Ratna Pancawati (MENGABDI : Jurnal Hasil Kegiatan Bersama Masyarakat, 2023)
Micro, Small and Medium Enterprises have a very important role in the national economy. One of the drivers of MSMEs is women who contribute 64% of Indonesian MSMEs. Finance has a very important role in starting a business. Based on the information we got, it can be concluded that Dharma Wanita mothers are still confused about how to start a business from their husband's limited income, therefore we help Dharma Wanita mothers how to manage their income so that they can set aside part of their income which will be used as capital in starting a business. The method of implementing this service is carried out by means of presentations and interactive discussions. The result of this service was that the women of the Dharma Wanita Association of the National Park Hall were very enthusiastic about the event. This could be seen from the many questions asked related to family financial management